Discovery of benzenesulfonamide derivatives as potent PI3K/mTOR dual inhibitors with in vivo efficacies against hepatocellular carcinoma. Issue 5 (1st March 2016) - Chen, Ying; Zhang, Ling; Yang, Chao; Han, Jinsong; Wang, Chongqing; Zheng, Canhui; Zhou, Youjun; Lv, Jiaguo; Song, Yunlong; Zhu, Ju
Graphical abstract: Abstract: The phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway is related to cellular activities. Abnormalities of this signaling pathway were discovered in various cancers, including hepatocellular carcinoma (HCC). The PI3K/mTOR dual inhibitors were proposed to have enhanced antitumor efficacies by targeting multiple points of the signaling pathway. We synthesized a series of propynyl-substituted benzenesulfonamide derivatives as PI3K/mTOR dual inhibitors. Compound7k (NSC781406) was identified as a highly potent dual inhibitor, which exhibited potent tumor growth inhibition in the hepatocellular carcinoma BEL-7404 xenograft model. Compound7k may be a potential therapeutic drug candidate for HCC.